Caracterización del proceso de convergencia del marco contable NIIF para el grupo 1. (2020)
This article specifically refers to the characterization of the IFRS convergence process in Colombia for Group 1. The process as such of applying International Financial Reporting Standards does not only involve making changes at the accounting level in an organization; this set of standards has interference in the way the entity operates and the way it generates value. The intention of the academic exercise is therefore to examine how the transitional and adaptive process of this accounting framework has been for large companies (Group 1).